2021
DOI: 10.1007/s10508-021-01963-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Aggression Victimization and Perpetration in a German University Student Sample

Abstract: This study examined the prevalence of sexual aggression perpetration and victimization in a sample of 1,172 students (755 female, 417 male) from four universities in Germany. All participants were asked about both victimization by, and perpetration of, sexual aggression since the age of 14 years, using the Sexual Aggression and Victimization Scale (SAV-S). Prevalence rates were established for different coercive strategies, sexual acts, and victim–perpetrator relationships. Both same-sex and opposite-sex victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Although this review demonstrated that most of the studies followed a gender inclusive approach examining TDV among female and male adolescents from both the victim and perpetrator perspective, there is a lack of studies addressing sexual minorities and studies including different gender identities. Given that previous evidence has shown that young adults who have same‐sex or both same‐ and opposite‐sex sexual contacts or those who self‐identify as sexual minorities, are more vulnerable to experience or/and to perpetrate sexual aggression (e.g., Canan et al., 2019; Krahé et al., 2021), more research addressing violence in these groups is needed. Furthermore, future research on violence in adolescent relationships should also pay more attention to other vulnerable groups, such as people with disabilities, or refugees, because in these groups, even higher prevalence rates of violence might be expected (e.g., Basile et al., 2016; De Schrijver et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although this review demonstrated that most of the studies followed a gender inclusive approach examining TDV among female and male adolescents from both the victim and perpetrator perspective, there is a lack of studies addressing sexual minorities and studies including different gender identities. Given that previous evidence has shown that young adults who have same‐sex or both same‐ and opposite‐sex sexual contacts or those who self‐identify as sexual minorities, are more vulnerable to experience or/and to perpetrate sexual aggression (e.g., Canan et al., 2019; Krahé et al., 2021), more research addressing violence in these groups is needed. Furthermore, future research on violence in adolescent relationships should also pay more attention to other vulnerable groups, such as people with disabilities, or refugees, because in these groups, even higher prevalence rates of violence might be expected (e.g., Basile et al., 2016; De Schrijver et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lavoie et al. (2002) have demonstrated that in a sample of male adolescents, perceived parental monitoring at late childhood was indirectly negatively associated with dating violence perpetration at the age 16–17 via antisocial behavior at the age of 15. Moreover, based on a recent meta‐analysis provided by Spencer et al.…”
Section: Introductionmentioning
confidence: 86%
“…Finally, different aspects of family influence have been studied in connection to TDV victimization and perpetration until now (see Hébert et al., 2019; Spencer et al., 2020, 2021, for meta‐analyses). Based on the Social Control Theory (Hirschi, 1969), one of the important predictors for TDV is parental monitoring , which has been confirmed in many studies (e.g., Foshee et al., 2012; Lavoie et al., 2002; Leadbeater et al., 2008; Miller et al., 2009).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most research on sexual aggression perpetration has focused on men (e.g., Abrahams et al, 2014), although sexual aggression is also perpetrated by women (see Fisher & Pina, 2013). In a large sample of college students in Germany, 9.4% of women reported sexual aggression perpetration towards men (Krahé et al, 2021). Studies using the same methodology in Turkey and Chile revealed female perpetration rates of 14.2% and 16.5%, respectively (Schuster et al, 2016a, b).…”
Section: Prevalence Of Sexual Aggressionmentioning
confidence: 99%